ANALISIS PENGGUNAAN BAHAN AJAR DIGITAL DALAM PEMBELAJARAN IPA DI SDN KONDANG 01 - Nurhalimah, Hani; Regina Lichteria Panjaitan; Ismail , Ali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the use of digital teaching materials in science learning at SDN Kondang 01. The research uses a qualitative approach with a case study approach. Data was obtained through observation, structured interviews with two teachers who used digital teaching materials in science learning and documentation. The focus of the study includes identifying needs, supporting factors, obstacles faced, and the impact of the use of digital teaching materials in science learning. The findings show that learning videos from the YouTube platform are the most frequently used digital media because they are able to convey material visually and attractively, making it easier for students to understand. The success of the use of digital teaching materials is supported by the availability of devices such as laptops, projectors, internet networks, and teachers' skills in operating technology. However, the learning process still faces a number of challenges, such as network disruptions, limited student devices, and technical obstacles such as power outages or damaged equipment. The use of digital teaching materials has a positive influence, including increasing students' enthusiasm and motivation to learn, making it easier for teachers to deliver abstract material and encouraging teachers to continue to develop competence and creativity. To overcome the barrier, teachers implement strategies such as downloading video materials first or combining digital learning with hands-on practice. This study recommends the need to improve infrastructure and technology training facilities for teachers to support the optimization of digital teaching materials in science learning at the elementary school level.